Composting of model kitchen waste using tempeh and tapai as microbial inoculants - Lee, Chew Tin (2015)
In this study, the composting materials consisting of model kitchen waste, dried leaves and rice bran were inoculated with four formulation of microbial inoculants namely 100% Tempeh (Te), 100% Tapai (Ta), 50% Tempeh +50% Tapai (Te+Ta), Effective MicroorganismTM (EM) and water as control. It was found that the temperature of all four composting materials with microbial inoculants can be heat up to temperature above 50oC than the control. The enzymatic activities were not able to indicate significant differences between the inoculated compost against the control. The highest activity of amylase (73-129 U/g) and cellulase (75-148 U/g) occurred at the beginning of the composting process. The maximum activities of lipase (5- 10 U/g) and protease (46-72 U/g) were observed at the middle stage of the composting process. However, the results suggested that Tempeh and Tapai can be used as microbial inoculants to degrade kitchen waste as their performance was comparable with EM. The necessities of using inoculants in composting of kitchen waste need to be further verified by maturity, stability and quality test on the matured composts.